A Review on Microgrids for Remote Areas Electrification-Technical and Economical Perspective - Erona Khatun; Md. Momin Hossain; Md. Sumon Ali; Md. Abdul Halim (International Journal of Robotics and Control Systems, 2023)
The main objective of this study is to review microgrids from both a technical and financial standpoint in order to electrify rural places. Making a microgrid in rural area is challenging due to its technical and economical perspective. Technical and Economic analysis could investigate power quality and system stability for a local community in a nation. The technical and economic aspects of microgrid design and operation are covered, along with a number of other parts such power sources, energy storage, and control systems. Installation and maintenance cost has been discussed with respect to technological and economical view point in this paper. The report ends with a review of the prospects and problems for implementing microgrids in remote locations. Various challenges of microgrid and prospective solutions have also been discussed for the betterment of microgrid technically and economically. Microgrid planning has also been explained in this paper in rural regions entails the process of creating, developing, and deploying microgrid systems to provide dependable and sustainable power. Some influential factors such as technological factors, economic factors, socio-political factors and environmental factors on which microgrid depends have been discussed in this paper. The study offers a thorough discussion of microgrids as a potential method for electrifying rural areas. The study shows that microgrid is economically more beneficial to be developed in any rural area, as well as complying the minimum technical requirement of local grid code. Therefore, it can be said that any locality of a nation is a more viable and economic location to implement microgrid for the development. This review will assist the decision-makers in adopting microgrids for the electrification of rural areas and hold establishing regulations that are helpful and clear for the operation and integration of microgrids. System effectiveness, energy storage, and grid management breakthroughs may result from research and development of microgrid technology.